Analisis Semiotika Konsep Patriarki dalam Film “Ngeri-Ngeri Sedap” Karya Bene Dion - Ginting, Christoper Arung; Vita, Nadra Ideyani (Universitas Medan Area, 2025)
Movies not only function as entertainment but also as a medium of communication that represents social, cultural, and ideological realities. This study analyzes the concept of patriarchy in Bene Dion's film Ngeri-Ngeri Sedap using the Roland Barthes semiotic approach. With qualitative research methods and case studies, this study examines how signifiers such as dialogue, expression, and interaction between characters form signified that reflect the dominance of men in the Batak family. The myths built in this film reinforce the understanding that patriarchy is a natural and hereditary system. The results of the study show that this film features patriarchy as an integral part of Batak culture, where men play the role of the main decision-makers and women are positioned as followers. This representation is not only seen in the relationship between husband and wife but also in the dynamics between boys and girls. This study contributes to the study of communication and gender by opening up further discussions about how film as a medium can maintain or critique existing social structures.